Heat shock protein (HSP) expression and mitogen-activated protein kinase (MAPK) phosphorylation during early embryonic developmental stages of the Gilthead sea bream (Sparus aurata) - ROUFIDOU, CHRYSOULA; FEIDANTSIS, KONSTANTINOS; MENTE, ELENI; SARROPOULOU, ELENA; ANTONOPOULOU, EFTHIMIA (Mediterranean Marine Science, 2018)
Both heat shock proteins (HSPs), which have key roles in vital cell functions, as well as members of the mitogen-activated protein kinases (MAPKs), which adjust gene expression by transducing cellular signals to the nucleus, are necessary for normal embryonic development in vertebrates. Therefore, protein expression levels of HSP70 and HSP90 and the activation of members of the MAPK protein family, such as p38 MAPK, ERKs, and JNKs were studied in the early developmental stages of the Gilthead sea bream, Sparus aurata Linnaeus, 1758. The protein expression of HSP70 and the phosphorylation ratio of JNKs remained at equal levels at all examined developmental stages, while the other examined proteins exhibited a differential profile. HSP90 levels were mostly increased at the 16-cell stage and towards the morula stages, and the lowest values were observed at the two- to four-cell and one-half epiboly stages. While p38 MAPK phosphorylation ratio exhibited increased values mostly in the early developmental stages, the opposite was observed concerning ERK phosphorylation ratio, where increased values were observed in the later embryonic stages (high blastula to one-half epiboly stages). These differential profiles of the examined protein expression levels highlight the importance of these proteins during embryogenesis and pave the way for further research to unveil their distinct role in early development.